2015
DOI: 10.3171/2014.11.jns141160
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for facial nerve schwannomas: a multicenter study

Abstract: F acial nerve schwannomas (FNSs) are rare tumors accounting for 1.9% of all intracranial neuromas and 0.8% of intrapetrous tumors.1 FNS can arise from any segment of the facial nerve, starting at its origin in the cerebellopontine angle and extending to its extracranial components.2 While such neuromas can mimic the radiographic features of the more common vestibular schwannoma, patients with FNS typically present with signs and symptoms of facial nerve dysfunction.The optimal management strategy for FNS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Several publica-tions report that Gamma Knife surgery has good results in terms of control of growth and symptoms with a small rate of radiation toxicity. [17][18][19] There are no published data about the malignant transformation of a FNS after SRS. For large or growing tumors with favorable FNF (HB < III), the choice of treatment should be discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Several publica-tions report that Gamma Knife surgery has good results in terms of control of growth and symptoms with a small rate of radiation toxicity. [17][18][19] There are no published data about the malignant transformation of a FNS after SRS. For large or growing tumors with favorable FNF (HB < III), the choice of treatment should be discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery(SRS) was described in the management of facial nerve schwannomas by various authors. [20][21][22] However, specific literature on the use of SRS in GSPN schwannoma is not available, in view of the rarity of the condition. SRS is a feasible option in small facial nerve schwannoma and should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The facial nerve tumors treated by SRS have reported excellent results with tumor control in 90 to 100% of the patients with reliable radiographic follow-up. 20,21 Sheehan et al reported that the actuarial tumor control was 97%, 97%, 97%, and 90% at 1, 2, 3, and 5 years after radiosurgery. 21 Overall, patients with smaller tumor volumes, low grade (H&B) facial weakness, and patients with < 50 db hearing loss at presentation tend to do better in terms of preservation of nerve functions after Gamma Knife radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key turning point in worldwide utilization of Gamma Knife radiosurgery (GKSRS) was its first North American installation at the University of Pittsburgh in 1987 [2]. Gradually and steadily, GKSRS has been demonstrated to be a highly successful modality in managing many benign and malignant indications [3][4][5][6][7][8][9]. However, due to the finite beam collimation size (maximum beam collimator diameter of 1.6-1.8 cm) and manual setups of individual patients, majority of the targets treated are relatively small lesions (e.g., <4 or 5 cm in maximum target dimension) and are generally treated in a single fraction [6,9].…”
Section: Hypofractionated Gamma Knife Radiosurgerymentioning
confidence: 99%